Surgical Repair of a Giant Unruptured Left Sinus of Valsalva Aneurysm in an Older Patient: A Case Report - Shinichi Oki; Hirotaka Sato (Clinical Case Reports)
ABSTRACT A giant unruptured left sinus of Valsalva aneurysms is extremely rare. Even if asymptomatic, surgical repair should be performed, considering comorbidities, and patient's physical condition. In this case, patch repair with coronary artery bypass, correction of sinotubular junction, and aortic annulus for aortic regurgitation benefited the older patient.